Accurate and efficient computations of phase-changing flows in thermal vapor compressors. (5th January 2018) - Min, Daeho; Kim, Hyeongjun; Lee, Hoon; Lee, Chaesoo; Kim, Chongam
Abstract: This paper focuses on the limitations of single-phase computations which have been widely applied to the numerical simulations of flow fields around thermal vapor compressors (TVCs), and provides computational improvements through multi-phase flow modeling and analysis. In order to capture the multi-phase flow physics accurately and provide reliable results, several numerical methods and models, including the shock-stable multi-phase AUSMPW+ scheme, phase-changing models, cell-by-cell adaptive mesh refinement technique, and the IAPWS-97 equation of states, are combined into a numerical solver. We then simulate various TVC systems and compare the computed system performance and local flow physics between the single- and multi-phase computations. Based on the computational results and comparisons, we examine phase-changing process and its influence on two major local physical features, namely shock-train region and shear layer.